2019
DOI: 10.3390/w11030626
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Heavy Metal (Ni, Mn, Co, Zn, Cu, Pb, and Fe) and PAH Content in Stormwater Sediments Based on Weather and Physico-Geographical Characteristics of the Catchment-Data-Mining Approach

Abstract: The processes that affect sediment quality in drainage systems show high dynamics and complexity. However, relatively little information is available on the influence of both catchment characteristics and meteorological conditions on sediment chemical properties, as those issues have not been widely explored in research studies. This paper reports the results of investigations into the content of selected heavy metals (Ni, Mn, Co, Zn, Cu, Pb, and Fe) and polycyclic aromatic hydrocarbons (PAHs) in sediments fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The next step was to determine the initial and boundary conditions [52]. In the analysis, in terms of boundary conditions, the grey water inflow rate was 40 °C at 9 L/min and the same was the CFD modeling (computational fluid dynamics) is a computer method, which helps to analyze and solve problems connected with the flow of liquids and gases.…”
Section: Swot/tows Analysis Of Dwhr Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The next step was to determine the initial and boundary conditions [52]. In the analysis, in terms of boundary conditions, the grey water inflow rate was 40 °C at 9 L/min and the same was the CFD modeling (computational fluid dynamics) is a computer method, which helps to analyze and solve problems connected with the flow of liquids and gases.…”
Section: Swot/tows Analysis Of Dwhr Systemsmentioning
confidence: 99%
“…The next step was to determine the initial and boundary conditions [52]. In the analysis, in terms of boundary conditions, the grey water inflow rate was 40 • C at 9 L/min and the same was the volume flow of cold water of 10 • C. The outflow of grey water from the heat exchanger was provided by setting the outlet pressure of 0 Pa.…”
Section: Potential Impact and Uncertainty Of Dwhr Systemsmentioning
confidence: 99%
“…A similar situation applies to roadside inlets (marked No. Figure 2), whose structure also foresees sedimentation elements capturing polluting items of larger size [25]. Systems also incorporating runoff from roads include sediment wells (marked No.…”
Section: Malodorous Gases In the Sewer Systemmentioning
confidence: 99%
“…The GWR model was used for spatial prediction of trace metal concentrations in surface and ground waters based on spatial predictors in Pakistan [29]. The statistical models developed by Bąk et al [30] for forecasting the quality of stormwater sediments, in which artificial neural networks are used (multilayer perceptron neural networks), showed varied impacts of catchment characteristics and atmospheric conditions on the chemical composition of sediments. The authors of these investigations concluded that the concentration of heavy metals (Ni, Mn, Co, Zn, Cu, Pb, and Fe) in sediments was far more affected by catchment characteristics (land use, length of the drainage system) than by atmospheric conditions.…”
Section: Introductionmentioning
confidence: 99%